Exploring the influences on classroom-based contact via shared education in Northern Ireland. Issue 1 (1st January 2017) - Loader, Rebecca
Abstract: Initiatives in intercultural education have frequently involved the promotion of contact between members of different groups as a means of improving intergroup relations. Experience from Northern Ireland suggests, however, that such schemes have often been organised and delivered in such a way that opportunities for sustained, high-quality contact are limited. This paper considers processes of contact in one relatively recent initiative, "shared education", which involves collaboration between separate schools to deliver classes to Catholic and Protestant pupils in mixed groups. Employing qualitative methods of observation and interviewing to capture participants' experiences of contact, the research explores the influences on the quality and frequency of cross-group interaction in the shared class. With findings highlighting the subject and pedagogy, teacher's approach and classroom arrangement as key factors, the study offers suggestions for policy and practice to enhance opportunities for contact and relationship-building in mixed classes.